2018
DOI: 10.1371/journal.pone.0195654
|View full text |Cite
|
Sign up to set email alerts
|

Cancer growth and metastasis as a metaphor of Go gaming: An Ising model approach

Abstract: This work aims for modeling and simulating the metastasis of cancer, via the analogy between the cancer process and the board game Go. In the game of Go, black stones that play first could correspond to a metaphor of the birth, growth, and metastasis of cancer. Moreover, playing white stones on the second turn could correspond the inhibition of cancer invasion. Mathematical modeling and algorithmic simulation of Go may therefore benefit the efforts to deploy therapies to surpass cancer illness by providing ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Nonetheless, this is sufficient for the purposes of understanding how the internal dynamics of a tissue population induce cancer niches. Moreover, our work provides a first step in going beyond a (factorised) mean-field approach to evaluating cancer proliferation and growth [ 7 , 8 , 9 , 10 ]. A second limitation arises from the deterministic formulation of the transition dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, this is sufficient for the purposes of understanding how the internal dynamics of a tissue population induce cancer niches. Moreover, our work provides a first step in going beyond a (factorised) mean-field approach to evaluating cancer proliferation and growth [ 7 , 8 , 9 , 10 ]. A second limitation arises from the deterministic formulation of the transition dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…For a computational understanding of cancer niche construction, a 2D Ising model has been used to evaluate phase transitions between cancerous and healthy cells [ 7 , 8 , 9 ]. For example, [ 10 ] used the Ising Hamiltonian to model metastasis, where the updates in the energy function were modelled using mean-field approximations, i.e., only considering average interactions. This factorised approach is consistent with other applications of the Ising model for simulating cancer progression [ 7 , 8 , 9 ]; however, cell niches are the result of numerous mechanisms, both at the cellular and population level.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one study revealed possible hazardous effects associated with the playing of “Go” in individuals with seizure disorders [23]. The amounts of real and virtual playing of board games have increased recently and, as a result, the number of published studies assessing the effects of board game use has also increased [12, 13, 17, 19]. The increase in game play is likely due to the prevalence of computer systems in the current age of information and communication technology (ICT) and artificial intelligence (AI).…”
Section: Mind/body Changes Due To Board Game Usementioning
confidence: 99%
“…The tumor-immune system interaction in the TME can be formalized as a biological system [24]. Computational models of such a system are of great importance, since the analysis made possible by simulations can improve our comprehension of the process behind the disease [22,31,32].…”
Section: Related Workmentioning
confidence: 99%
“…In the ABM approach, simple agents represent the elements of cancer and of the IS [41]; the interaction between these results in a complex emergent behavior which is not restricted to the linear combination of the individual elements [42,43]; hence ABMs can incorporate the changes that bring about non-deterministic interactive processes [22,26,37].…”
Section: Related Workmentioning
confidence: 99%